Trichotillomania in a young male complicated by tinea capitis associated with Cryptococcus laurentii and Candida parapsilosis - Fellner MJ (Dove Medical Press, 2013)
Michael J Fellner Department of Dermatology, New York Medical College, New York, NY, USA Abstract: This is the first case report of tinea capitis associated with Cryptococcus laurentii as well as Candida parapsilosis in an eleven year old male which responded to treatments with griseofulvin, lamisil, as well as fluconazole only to show recurrent alopecia from an underlying problem of trichotillomania. When confronted with the biopsy diagnosis of trichotillomania, the family admitted knowledge of the hair pulling disorder for at least five years. It took three providers to finally solve the question of the recalcitrant alopecia. Keywords: tinea capitis, trichotillomania, lamisil, fluconazole, griseofulvin, cryptococcus laurentii, candida parapsilosis